Swift Functional Programming - Nayebi, Dr. Fatih; Nayebi, Dr. Fatih (Packt Publishing, 2017)
Bring the power of functional programming to Swift to develop clean, smart, scalable and reliable applications.About This BookWritten for the latest version of Swift, this is a comprehensive guide that introduces iOS, Web and macOS developers to the all-new world of functional programming that has so far been alien to themGet familiar with using functional programming alongside existing OOP techniques so you can get the best of both worlds and develop clean, robust, and scalable codeDevelop a case study on example backend API with Swift and Vapor Framework and an iOS application with Functional Programming, Protocol-Oriented Programming, Functional Reactive Programming, and Object-Oriented Programming techniquesWho This Book Is ForMeant for a reader who knows object-oriented programming, has some experience with Objective-C/Swift programming languages and wants to further enhance his skills with functional programming techniques with Swift 3.x.What You Will LearnUnderstand what functional programming is and why it mattersUnderstand custom operators, function composition, currying, recursion, and memoizationExplore algebraic data types, pattern matching, generics, associated type protocols, and type erasureGet acquainted with higher-kinded types and higher-order functions using practical examplesGet familiar with functional and non-functional ways to deal with optionalsMake use of functional data structures such as semigroup, monoid, binary search tree, linked list, stack, and lazy listUnderstand the importance of immutability, copy constructors, and lensesDevelop a backend API with VaporCreate an iOS app by combining FP, OOP, FRP, and POP paradigmsIn DetailSwift is a multi-paradigm programming language enabling you to tackle different problems in various ways. Understanding each paradigm and knowing when and how to utilize and combine them can lead to a better code base. Functional programming (FP) is an important paradigm that empowers us with declarative development and makes applications more suitable for testing, as well as performant and elegant. This book aims to simplify the FP paradigms, making them easily understandable and usable, by showing you how to solve many of your day-to-day development problems using Swift FP.It starts with the basics of FP, and you will go through all the core concepts of Swift and the building blocks of FP. You will also go through important aspects, such as function composition and currying, custom operator definition, monads, functors, applicative functors,memoization, lenses, algebraic data types, type erasure, functional data structures, functional reactive programming (FRP), and protocol-oriented programming(POP). You will then learn to combine those techniques to develop a fully functional iOS application from scratchStyle and approachAn easy-to-follow guide that is full of hands-on coding examples of real-world applications. Each topic is explained sequentially and placed in context, and for the more inquisitive, there are more details of the concepts used. It introduces the Swift language basics and functional programming techniques in simple, non-mathematical vocabulary with examples in Swift.